2010
DOI: 10.1111/j.1745-5871.2009.00607.x
|View full text |Cite|
|
Sign up to set email alerts
|

Study of the Impact of Urban Development on Surface Temperature Using Remote Sensing in Ho Chi Minh City, Southern Vietnam

Abstract: Rapid urbanisation and industrialisation have resulted in sharp land cover changes. Urban change not only impacts on land cover but also on urban climate. Land surface and atmospheric modifications due to urbanisation generally lead to a modified thermal climate that is warmer than the surrounding, non‐urbanised areas. In this research remote sensing technology was used to evaluate urban growth patterns and its thermal characteristics through mapping impervious surfaces and evaluating thermal infrared images. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 9 publications
3
28
0
Order By: Relevance
“…In addition, Bokaie et al [30] investigated the relationship between seasonal change in land surface temperature and land use/land cover (LULC) classes in Tehran in 2010 and concluded that UHI effects had different causes due to the type of LULC classes in the region. Similarly, Van and Bao [31] reported that the highest surface temperature cores were in industrial and urban areas, and land cover composed of forest or water showed lower temperatures. Hart and Sailor [32] showed that the area with the warmest air temperature was a locus associated with industrial use, possibly due to a lack of vegetation and constant anthropogenic heat release.…”
Section: Literature Review: Effect Of Urban Factors On Temperaturementioning
confidence: 81%
“…In addition, Bokaie et al [30] investigated the relationship between seasonal change in land surface temperature and land use/land cover (LULC) classes in Tehran in 2010 and concluded that UHI effects had different causes due to the type of LULC classes in the region. Similarly, Van and Bao [31] reported that the highest surface temperature cores were in industrial and urban areas, and land cover composed of forest or water showed lower temperatures. Hart and Sailor [32] showed that the area with the warmest air temperature was a locus associated with industrial use, possibly due to a lack of vegetation and constant anthropogenic heat release.…”
Section: Literature Review: Effect Of Urban Factors On Temperaturementioning
confidence: 81%
“…In recent decades, population growth and economic development have directly affected landscapes' transformations in developing countries [1]. Rapid changes in the landscape have resulted in the conversion of natural vegetation and agricultural land into built-up (impervious) land, such as buildings, parking lots, roads, and other constructions [1][2][3][4]. This has caused several environmental problems at local, regional, and global scales [5], such as decreases in agricultural land [6]; habitat destruction [5,7,8]; air, soil, and water contamination [9][10][11]; increases in vector-borne diseases, such as malaria and dengue [12]; decreases in green space [13,14]; and increases in land surface temperature (LST) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The process of urbanisation often replaces natural vegetation and agricultural land with impervious surfaces, such as buildings and roads (Thi Van and Xuan Bao, 2010). This trend has produced a series of environmental impacts on biodiversity, local climate, hydrologic processes, and so forth (Streutker, 2002; Roy et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have investigated the relationship between LST and LUCC (Chen et al ., 2006; Xiao and Weng, 2007; Thi Van and Xuan Bao, 2010) with two main foci. The first focus has been on the comparison of the LST of different land‐use conditions.…”
Section: Introductionmentioning
confidence: 99%